Proton radiotherapy dose perturbations caused by esophageal stents of varying material composition are negligible in an experimental model - Jalaj, Sujai; Lee, Sang Yeob; McGaw, Camille; John, Bijo K; Li, Zuofeng; Awad, Ziad T; Scolapio, James S; Munoz, Juan C (Endoscopy International Open, 2015)
Background: Self-expanding metal and plastic esophageal stents (SEMS and SEPS, respectively) are used in conjunction with chemoradiation for palliation of malignant dysphagia. To date, the dosimetric effects of stents undergoing proton radiotherapy are not known.Study aim: To investigate the proton radiotherapy dose perturbations caused by esophageal stents of varying designs and materials undergoing external beam treatment for esophageal cancer.Patients and methods: Simulated clinical protocol. Solid acrylic phantom was used to mimic the esophageal tissue environment. Stents made of nitinol, stainless steel and polyester were tested. Proton beam dose of 2 Gy-E was delivered to each stent in a single anterior to posterior field. Film and image based evidence of dose perturbation were main outcomes measured. Results: Only the stainless steel and plastic stents demonstrated slight overall dose attenuations (– 0.5 % and – 0.4 %, respectively). All the nitinol-based stents demonstrated minimal overall dose perturbations ranging from 0.0 % to 1.2 %. Negligible dose perturbations were observed on each of the stent surfaces proximal to the radiation source, ranging from – 0.8 % (stainless steel stent) to 1.0 % (nitinol stent). Negligible dose effects were also observed on the distal surfaces of each stent ranging from – 0.5 % (plastic and stainless steel stents) to 1.0 % (nitinol stent). Conclusion: Proton radiotherapy dose perturbations caused by stents of varying designs and material composition are negligible. Negligible dose perturbation is in keeping with the inherent advantage of proton therapy over traditional radiotherapy composed of photons – given its relative large mass, protons have little side scatter.